Evaluation of Perforator Fasciocutaneous Flaps for Oncoplastic Immediate Reconstruction Following Breast Conservative Surgery in Lower and Lateral Breast Quadrant Lesions Perforator Fasciocutaneous Flaps for OBCS - Mahmoud Ali Mohamed Abd El Mohsen; Ismail Ahmed Shafik; Shadin Hamza Hassan Abas; Mostafa Mahmoud Abdelfatah (European Journal of Breast Health)
Objective: To compare the oncological safety and the cosmetic outcome of the techniques anterior intercostal artery perforator (AICAP), lateral intercostal artery perforator (LICAP) and thoracodorsal artery perforator (TDAP) flap as a volume replacement technique to eliminate deformity and preserve breast cosmesis by filling the excised defect. Materials and Methods: This prospective study included women with lower outer quadrant, lower inner quadrant, and upper outer quadrant tumors who underwent upfront or post-neoadjuvant chemotherapy breast conserving surgery with immediate volume replacement surgery. Patients were allocated into three groups at a ratio of 1:1: Group A (n = 10): women who underwent LICAP flap, group B (n = 10): Women who underwent AICAP, and group C (n = 10): Women who underwent TDAP flap procedures. Results: Regarding postoperative complications, wound infection took place in only one (10%) patient in LICAP group and one (10%) patient in the AICAP group; seroma occurred in only one (10%) patient in LICAP group and one (10%) patient in the TDAP group; and fat necrosis occurred in only one (10%) patient in the TDAP group. Incidence of wound infection, seroma, and fat necrosis was insignificantly different among the studied groups. Breast distortion occurred in one (10%) patient in the AICAP group and not observed in the other groups, and partial flap necrosis occurred in one (10%) patient in the LICAP group and one (10%) patient in the AICAP group and was not observed in the TDAP group. Incidence of distortion and partial flap necrosis were insignificantly different between the studied groups. The conservative treatment of breast cancer core results, surgeon’s assessment, patient’s satisfaction and breast Q scores did not differ between the three groups. Conclusion: A better cosmetic outcome than level II oncoplastic techniques, the perforator fasciocutaneous flaps, LICAP, AICAP, and TDAP, were effective and safe options for immediate breast reconstruction after breast-conserving surgery. All three techniques showed similar surgical outcomes, low complication rates, and good aesthetic results. Patient satisfaction was high, with no significant differences between the groups.